IDENTIFIKASI POTENSI FINANCIAL DISTRESS MENGGUNAKAN RASIO KEUANGAN PADA PERUSAHAAN SEKTOR INDUSTRI MANUFAKTUR - Azira Vella Safa; Cahyani Nuswandari (Jurnal Ilmiah Akuntansi Peradaban, 2022)
This study aims to examine and analyze the effect of liquidity ratios, profitability ratios, activity ratios, and leverage ratios on financial distress. The object of research used is the manufacturing industry sector companies listed on the Indonesia Stock Exchange (IDX) for the 2017-2020 period. This research uses logistic regression analysis method. The technique in selecting the sample is non-probability sampling with a purposive sampling approach which produces a total of 649 data. The results showed that the liquidity ratio had no effect on financial distress, the profitability ratio had a negative effect on financial distress, the activity ratio had a negative effect on financial distress, and the leverage ratio had a positive effect on financial distress. Keyword: Liquidity Ratio, Profitability Ratio, Activity Ratio, Leverage Ratio, Financial Distress